2020
DOI: 10.21529/recadm.2020004
|View full text |Cite
|
Sign up to set email alerts
|

Identificar-se com os outros Consumidores Minimiza o Efeito Crowding? O papel da similaridade percebida

Abstract: O estudo propõe que a identificação do consumidor com os outros clientes que compartilham o mesmo ambiente de loja minimiza o efeito crowding. Assim, investigou-se de que modo a similaridade percebida modera a direção dos efeitos da densidade humana sobre a percepção de crowding, bem como da percepção de crowding sobre a satisfação do consumidor. A partir de um estudo de desenho experimental, hipóteses de pesquisa foram testadas, e os achados evidenciam que a similaridade percebida contribui para que o efeito … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0
12

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 68 publications
(73 reference statements)
0
1
0
12
Order By: Relevance
“…Perceived human crowding has also been defined as the maximum amount of people who can use a site without an unacceptable alteration in the physical environment or an acceptable quality of the visitor experience ( Sanz-Blas, Buzova, & Schlesinger, 2019 ; Wall & Mathieson, 2006 ; Zehrer & Raich, 2016 ). Previous research has confirmed that subjective psychological factors (such as consumer expectations and preferences, perception of other customers, or social inclusions), or objective factors (such as actual visitor encounters) can influence the perception of crowding ( Aguiar & de Farias, 2020 ; Budruk, Schneider, Andreck, & Virden, 2002 ; Sivey, McAllister, Vally, Burgess, & Kelly, 2019 ). Perceived severity of crowding also correlates significantly with the level of satisfaction derived from an activity ( Huang, Huang, & Wyer, 2018 ; Moharana & Pradhan, 2019 ; Shelby & Heberlein, 1986 ; Sim, Koo, Koo, & Lee, 2018 ; Thomas & Saenger, 2018).…”
Section: Literature Reviewmentioning
confidence: 98%
“…Perceived human crowding has also been defined as the maximum amount of people who can use a site without an unacceptable alteration in the physical environment or an acceptable quality of the visitor experience ( Sanz-Blas, Buzova, & Schlesinger, 2019 ; Wall & Mathieson, 2006 ; Zehrer & Raich, 2016 ). Previous research has confirmed that subjective psychological factors (such as consumer expectations and preferences, perception of other customers, or social inclusions), or objective factors (such as actual visitor encounters) can influence the perception of crowding ( Aguiar & de Farias, 2020 ; Budruk, Schneider, Andreck, & Virden, 2002 ; Sivey, McAllister, Vally, Burgess, & Kelly, 2019 ). Perceived severity of crowding also correlates significantly with the level of satisfaction derived from an activity ( Huang, Huang, & Wyer, 2018 ; Moharana & Pradhan, 2019 ; Shelby & Heberlein, 1986 ; Sim, Koo, Koo, & Lee, 2018 ; Thomas & Saenger, 2018).…”
Section: Literature Reviewmentioning
confidence: 98%
“…No que se refere às atitudes e comportamentos de compra em ambientes de varejo, estudos evidenciaram que a presença social pode atuar como agente moderador, tanto no que diz respeito aos clientes, como das pessoas detentoras de serviços do varejo. Além disso, a presença e o comportamento de outros consumidores, possuem um grande impacto na medida que influenciam diretamente na percepção dos indivíduos quanto a qualidade dos serviços, bem como podem interferir nas reações individuais do consumidor, sejam elas comportamentais, afetivas ou atitudinais (Baker, 1986;Brocato et al, 2012;Aguiar & Farias, 2020).…”
Section: Referencial Teóricounclassified
“…Esse fenômeno influencia diretamente os consumidores no que se refere às suas emoções e percepções. Assim, à medida que há variação no estado emocional dos consumidores devido à maior ou menor percepção de crowding, existirão diferenças nas respostas comportamentais e avaliações da experiência de compra (Eroglu & Harrell, 1986;Brandão, 2012;Aguiar & Farias, 2020).…”
Section: Referencial Teóricounclassified
See 2 more Smart Citations